The attitude towards the new rice direct-seeding device. (2018) - Pramitithanakan, Dumrongdej; Tantayanon, Supawan; Wattanavichien, Kanit; Kunnoot, Laddawan
This study investigated users' behaviour concerning the attitude towards a new technology. The perceived characteristics of innovation, based on the diffusion of innovation theory, were selected as guidelines for data collection. A semi-structured in-depth interviewing qualitative technique was initially employed to assess the meaning of users' perceived characteristics of the rice direct seeding device. Members of three communities with high performances in rice producing were targeted purposively for the interviews. The data were analysed and rewritten as the content of the field survey questionnaire to measure the relation between the attitudes and the perceived characteristics. The questionnaires were assessed using a five-point Likert's scale. Cronbach's coefficient alpha was chosen for reliability testing. The respondents were rice producers. Multiple regression analysis qualitative technique was used to confirm the hypothesised relationships. The findings showed demographics and socio-economics, relative advantage, compatibility, complexity and observability influenced the attitude towards the direct seeding machine.